The FGFR inhibitor pemigatinib overcomes cancer drug resistance to KRAS G12C inhibitors in mesenchymal lung cancer - Angela Abdollahi; Margaret Favata; Michael Weber; Valerie Roman; Rodrigo Hess; Kayla Hammond; Matthew R. Farren; Mike Schaffer; Aidan Gilmartin; Hui Wang; Jonathan Rios-Doria; Alejandro Amador-Arjona (PLoS ONE, 2025)
KRAS mutations are high prevalence oncogenic drivers for multiple cancers. With the advent of new classes of KRAS inhibitors that are showing meaningful clinical activity, research is now turning to questions of optimal combinations of therapies for specific indications, as many patients with KRAS G12C mutations do not respond and/or develop resistance to single-agent treatment. Here, we investigate combination therapies that may overcome resistance to KRAS G12C inhibitors. We found that pemigatinib, a potent and selective FGFR1–3 inhibitor, had a significantly high Bliss synergy score in combination with KRAS G12C inhibitors, and FGFR1 activity was shown to decrease KRAS G12C-dependency conferring inherent resistance in mesenchymal-like cell lines. Knockdown experiments verified the importance of FGFR1, but not FGFR2-4, for the synergistic effect with KRAS G12C inhibitors. Additionally, human lung cancer xenograft and patient-derived xenograft models with a mesenchymal phenotype and high FGFR1 expression were sensitive to the combination of G12C inhibitors and pemigatinib. In short, we demonstrate that pemigatinib and KRAS G12C inhibitors are promising agents for combination therapy in non-small cell lung cancer with a mesenchymal-like phenotype harboring high FGFR1 expression and KRAS G12C mutations to broaden patient response.